2017
DOI: 10.1016/j.desal.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Electrically conductive spacers for self-cleaning membrane surfaces via periodic electrolysis

Abstract: The use of an electrically conductive membrane has attracted significant interest in water treatment technology due to remarkable performance in fouling mitigation domain. In electrochemical systems, when external potential is applied, water electrolysis occurs and the generated gases efficiently clean the membrane surface. However, fabricating and integrating conductive membranes in current water treatment modules is challenging. The present work applies, for the first time, the electrolysis concept at the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…An emerging methodology is to modify feed spacer configuration to reduce fouling. Generally, several strategies have been adopted to develop mesh-type spacers such as by surface coating [54], altered geometry design [55] or three-dimensionally printed feed spacers [41], and use of electrically conductive spacers [43].…”
Section: Effect Of Feed Spacer Modification On Foulingmentioning
confidence: 99%
See 3 more Smart Citations
“…An emerging methodology is to modify feed spacer configuration to reduce fouling. Generally, several strategies have been adopted to develop mesh-type spacers such as by surface coating [54], altered geometry design [55] or three-dimensionally printed feed spacers [41], and use of electrically conductive spacers [43].…”
Section: Effect Of Feed Spacer Modification On Foulingmentioning
confidence: 99%
“…As a result, application of the electrical potential to the electro-conductive feed spacer, rather than the membrane surface, is a promising alternative modification, wherein foulant mitigation either through oxidation (spacer acts as an anode in electrochemical system) [84] or bubble generation (spacers acts as a cathode) [85,86] to cause disruption and release of fouling layers. However, self -cleaning membrane fouling mitigation very challenging [43]. Baek et al [44] used a lab-scale crossflow setup with an electro-conductive feed spacer to simulate a SWM employed in industrial applications.…”
Section: -3 Electrically Conductive Feed Spacersmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the principal mechanism on which electrochemical membrane fouling mitigation is based [52]. However, it has recently been suggested that whilst bubble formation via electro-reduction is an efficient mechanism for in situ cleaning of membranes, the oxidation method may damage the membrane itself [55][56][57][58][59]. Bubbles offer a promising option for a clean, inexpensive and environmentally friendly technique appropriate for in situ cleaning of conducting substrates.…”
Section: Introductionmentioning
confidence: 99%